Alternative Use Of Roundabout As Storm Water Detention Pond - Mah, D.Y.S.; Ho, Tze Yung (JCECT, 2017)
This study explores the concept of utilising roundabout as a component of the urban stormwater system. The research team has developed a drainage model to incorporate a roundabout as dry detention pond. In addition, the model is used to determine the effectiveness of such design by applying the concept virtually on a real-world roundabout at the southeast of UniGarden, a housing estate situated about 17 km from Kuching City of Sarawak. Computer representations of the existing drainage system and roundabout dry detention pond are built using the USEPA SWMM software. The modelling effort shows that the open space provided by a large roundabout is capable of achieving the maximum attenuation of storm flows and is able to hold 100% of runoff from 100-year storm. As empty spaces are increasingly hard to come by in urban areas; therefore, using an open space in a roundabout for dry detention pond is a good example of an innovative drainage system.